Revitalisasi Nilai-nilai Imago Dei dalam Pembentukan Karakter Anak Pada Era Digital - Paembonan, Yanni; Ronda, Daniel (Institut Agama Kristen Negeri Toraja, 2024)
The digital era presents new challenges in shaping children's character. Technology, social media, and wide access to information often significantly influence children's mindsets, behaviors, and morality, distancing them from theological principles and Christian teachings. This research explores revitalizing